El Aguinaldo Campesino como manifestación festiva, popular y tradicional en el municipio de Tuta Boyacá: estudio creativo en la cátedra de danzas andinas 2019-ll - Alba Bolívar, Carlos Iván (Universidad Antonio Nariño, 2022)
This degree work called El Aguinaldo Campesino as a manifestation festive, popular and traditional in the municipality of Tuta, Boyacá: the Systematization of the process from the Chair of Andean Dances 2019-II and the EAPEAT to the final assembly, it is carried out as part of the requirements for the culmination of my training process as a master artist of the Bachelor of Art Education with Emphasis in Dance and Theater; their developments, contributions, scope, questions and projections contribute to the strengthening of the Didactic Arts Research Group Scenic, and is part of the line that bears the same name. In particular, it It is part of the studies of the Tradition and Artistic Production sub-line. As such, the systematization of the EAPEAT in the second half of 2019, which supports significantly in terms of recovering, reflecting and systematizes the process lived during the exit to this place, one of the elements that make up the non-material culture, are its traditions, celebrations and festivals. Memories that beyond the space of pastime, rest, play and rejoicing, are some of the main manifestations of culture, it is defined as a set of experiences that are forgotten from generation to generation. For other On the other hand, customs are those social practices rooted in a community, linked to everyday life, with habits that from being repeated so much have become part of the local identity (Abadía, 1983; Romero, 2021) According to (Fernández, 2007), popular festivals, an important segment of the tradition of a people or territory, enclose an indivisible whole that starts from things what people “believe (field planting practices, family traditions), do (dance, music), he knows (illnesses, food), even the ones he counts 12